Dampak Defisiensi dan Toksisitas Hara Magnesium terhadap Karakteristik Agronomi dan Fisiologi Padi Gogo - Novita, Aisar; Tampubolon, Koko; Julia, Hilda; Fitria, Fitria; Hapsani Hasan Basri, Arie (Perkumpulan Agroteknologi/Agroekoteknologi Indonesia, 2022)
Deficiency or excess magnesium in the soil can affect the vegetative and generative growth of plants. This study aimed to identify the effect of magnesium deficiency and toxicity on the agronomic and physiological characteristics of upland rice. The study was conducted on farmers' land, Medan Selayang Subdistrict, Medan City, from June 2021 to January 2022. This study used a non-factorial randomized block design, namely the application of 27% MgO fertilizer based on the deficiency rates, (0; 1/2; 1/4; 1/8; 1/16; 1/32 times), while the toxicity levels include 0; 2; 4; 8; 16; 32-times within three replicates. The results showed that Mg deficiency significantly inhibited the growth of plant height; leaf area; total chlorophyll SPAD; panicle length; shoot dry weight; and yield.ha-1 were 20.68; 26.77; 19.23; 22.60; 44.20; and 50.72%, respectively. The Mg toxicity significantly inhibited the growth of the leaf area, the number of tillers, number of productive tillers, shoot dry weight, and root dry weight were 14.24; 32.15; 42.87; 34.07; and 44.31%, respectively. The critical limit (BK50) for upland rice caused by deficiency and toxicity of Mg were 0.032 and 1125.189 g/10 kg of the soil, respectively.